(untitled) (Progressive Agriculture, 2019)
Mechanical intervention in each stage of post-harvest operation of paddy is time demand due to increased cost of labour as well as shifting of labour from agriculture to non-agriculture sector. Mitigation of food demand of rapidly increasing population is becoming a major future challenge in agriculture sector. Drying of paddy is important for maintaining quality and long term storage of paddy. Among the drying methods, traditional sun drying is the most common practice in Bangladesh. Normally, farmers use yard in wet season (Boro & Aus) and field in dry season (Aman) to dry paddy. In this case, appropriate paddy drying technology could play a vital role to strengthen food security by reducing drying loss. Therefore, a study was conducted to investigate the drying loss of paddy both in traditional sun drying and mechanized drying method (BAU-STR dryer) at selected areas of Bangladesh. Popular and mega rice varieties cv. BRRI dhan28 and BRRI dhan49 were used as drying materials to evaluate the performance of BAU-STR dryer with different dryer capacity i.e. 300, 400, 500 and 600 kg of paddy per batch. Drying losses of BAU-STR dryer were examined during Boro and Aman season of 2015 and 2016 whereas drying losses under open sun drying method was measured during Aman season 2017 in the selected areas of Tangail, Mymensingh, Netrokona and Jessore districts of Bangladesh. The results showed that the average drying loss of paddy in BAU-STR dryer was found 0.48% and 0.36% during Boro and Aman seasons, respectively at 2015 and 2016 while sun drying loss at farmer’s field level was found 3.95, 3.24, 2.98 2.41 and 3.04% in Tangail, Mymensingh (Phulpur), Mymensingh (BAU), Netrokona and Jessore districts, respectively. The low cost BAU-STR dryer would be an alternative and effective drying technology to save 1.4 MMT of paddy by reducing 2.7% losses of national production (51.87 MMT) for combating hunger and improving food security in Bangladesh. Progressive Agriculture, Vol. 30, Suppl. 1: 42-50, 2019